Endometrial cell-derived conditioned medium in combination with platelet-rich plasma promotes the development of mouse ovarian follicles. Issue 1 (2nd November 2022) - Taghizabet, Neda; Rezaei-Tazangi, Fatemeh; Mousavi, Mahboubeh; Dehghani, Farzaneh; Zareifard, Nehleh; Shabani, Soha; Bahmanpour, Soghra; Aliakbari, Fereshteh; Sadeghzadeh, Zahra; Dortaj, Hengameh; Chakerzehi, Arezoo; Mohseni, Gholamreza
Summary: Fertility preservation is one of the most important issues in assisted reproductive technology. Previous studies have shown that cytokines and growth factors can improve follicle growth. The endometrial stromal cells secrete various factors that are involved in maintaining the integrity of uterine and epithelial secretory function. The platelet-rich plasma contains a large assembly of platelets suspended in plasma that successfully improves the viability and growth of various cell lines. This work aimed to investigate the influences of conditioned medium (CM) and platelet-rich plasma (PRP) on the development of ovarian follicles in infertile mice due to cyclophosphamide (CYC) exposure. In this study, 65 healthy BALB/c female mice (∼28–30 g and 6-8 weeks old) in five groups were studied. Immunohistochemistry (IHC) was used to detect growth differentiation factor 9 (GDF9)-positive cells. The mRNA expression levels of SMAD1, SMAD2, and BMP15 was assessed using reverse transcription-polymerase chain reaction (RT-PCR) method. The expression levels of SMAD1, GDF9, BMP15, and SMAD2 in the CM+PRP group was significantly more than in the CM and PRP groups. In addition, live birth occurred in the CM+PRP group. Treatment with CM+PRP in infertile mice due to Cy exposure increased fertility and live-birth rate. In general, our study suggested that the CM and PRP combination could improve the growth of mice ovarian follicles in vivo.